Cell position and light influence C4 versus C3 patterns of photosynthetic gene expression in maize. - Langdale, J A (1988)
C4 plants such as maize partition photosynthetic activities in two morphologically distinct cell types, bundle sheath (BS) and mesophyll (M), which lie as concentric layers around veins. We show that both light and cell position relative to veins influence C4 photosynthetic gene expression. A pattern of gene expression characteristic of C3 plants [ribulose bisphosphate carboxylase (RuBPCase) and light-harvesting chlorophyll a/b binding protein in all photosynthetic cells] is observed in leaf-like organs such as husk leaves, which are sparsely vascularized. This pattern of gene expression reflects direct fixation of CO2 in the C3 photosynthetic pathway, as determined by O2 inhibition assays. Light induces a switch from C3-type to C4-type gene expression patterns in all leaves, primarily in cells that are close to a vein. We propose that light causes repression of RuBPCase expression in M cells, by a mechanism associated with the vascular system, and that this is an essential step in the induction of C4 photosynthesis.